Análise da relação entre os mecanismos de governança pública e a execução de convênios federeais - Moraes, Larissa Siqueira (2018)
The base of this work is Jesuits Pedagogy and their manager practice contend in Ratio Studiorum rules, under a memoir aspect, aiming to understand Jesus Company members’ education and formation. The Practical Manual with 467 rules, on 1599 last version, which include those teaching bounded, contending more important elements are administration, curriculum and methodology. Based on theoretical reflection and collected data about this theme, we discuss some mediation that still appear to be establish on management practice, under Ratio Studiorum perspective. Data analysis basis is hermeneutic method – considering hermeneutic comprehensive possibility allow that education become elucidated to itself on very own justification basis, through debating about rationalities acting on pedagogic doing. After heuristic realization, in other words historic documents and sources research, followed by interpretation of collected information. The methodological chosen path is qualitative and exploratory, within bibliographic research for systematization and analysis of school administration legal and theory outline on first Jesuitical school times, which had Ratio Studiorum as their great depositary of educational standards and precepts in XVI Century. These observations induced us to believe Ratio Studiorum is very important for educational manegment memory and jesuitical pedagogic method makes possible to comprehend mainful aspects of Jesus Company schools organization. Besides presenting guidance for methodology and content to be elaborated in courses, the document is about each school member responsibility. We understand Ratio Studiorum as a path that makes possible to reach the meaning of educational existance, which could conduct all congregation through decades. For jesuitic pedagogy instruction and education walked together, however we should not consider these processes as strictly religious and used to promote the true religion. Our research obviously does not has everything could be extracted from Ratio Studiorum, it is just an add to others which also have Ratio as study object, and could be guidance for new works and still presents many nuances and view. We emphasize management view, but other aspects of this document could be analyzed. Considering, in the end, Ratio Studiorum as a study field with great potential and still has a lot to contribute to memory, management and education knowledge.